EXTRACTION CHARACTERISTIC AND MICROENCAPSULATION OF ANTOCYANIN AS NATURAL FOOD COLOURING FROM ROSELLE CALYCES BY ULTRASOUND-ASSISTED EXTRACTION (Universitas Negeri Semarang, 2017)
Anthocyanins are widely used as a food additive, and further study in production process development is required in order to obtain an efficient and superior process. This article presents the anthocyanin extraction by ultrasound-assisted extraction and the characterization of solid form anthocyanin extract. In addition, a simple kinetic analysis for the extraction process is investigated. Extraction was conducted by ultrasound-assisted extraction with a solute-solvent ratio of 1:4 and 1:8 at a temperature of 30OC, 40OC and 60OC. Anthocyanin content was analyzed by UV-VIS spectrophotometer. Drying process was performed by a freeze dryer with the addition of maltodextrin and followed by characterization of powder comprising moisture content, solubility and colour intensity. The result shows that the extraction temperature has an effect on anthocyanins extracted. Temperatures rise increased the diffusion coefficient and triggered the driving force of solids into the solvent. This result had a correlation with the second-order kinetic model where the rate of extraction increases along with temperature rise. Characterization of anthocyanin extracts in solid form showed that the addition of maltodextrin provided better results than the product without maltodextrin. The anthocyanin powder added with maltodextrin fulfils the Indonesian standards for food colouring powders, having a low moisture content (5.6%) and high solubility (91.4%). Moreover, colour intensity analysis of anthocyanin powder showed that the powder with maltodextrin has a tendency of a lighter colour with low value of L *, a * and b *.